Principles of ecotoxicology - Walker, C. H. (CRC Press, 2012)
"Now in its fourth edition, this exceptionally accessible text provides students with a multidisciplinary perspective and a grounding in the fundamental principles required for research in toxicology today. Its concisesness and readability makes it highly popular with students, while its focus on principles makes its the preferred choice of instructors.Discussing the fundamental chemical and ecological nature of pollution processes, the authors identifiy the major classes of pollutants and their environmental fate while examining those pollutants deserving closer scrutiny. They also cover naturally occurring poisons, the history of chemical warfare, population risk assessment, community structure, neonicotinoids, endocrine disruption, neurotoxicity, and the employment of biomarker strategies in field studies. In addition to updating the text throughout, this fourth edition--Includes a new chapter on future directions of ecotoxicologyProvides new material on nanoparticle pollution and effects of chemical weaponsOffers numerous new case studies, many from the U.S.Expands coverage of bioaccumulation, biomarkers, and risk assessment for affected populations "--